2014
DOI: 10.1891/0886-6708.vv-d-12-00171
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Borderline Personality Disorder and Depression in the Relationship Between Sexual Assault and Body Mass Index Among Women Veterans

Abstract: This article examines lifetime sexual assault (LSA) and mental health history as risk factors associated with body mass index (BMI) in a population of women veterans. This cross-sectional study of a retrospective cohort of 948 Veterans Affairs (VA)-enrolled midwestern enlisted rank women veterans included computer-assisted telephone interviews. Findings show that 33.4% of the participants had a BMI of 30.0 or more meeting the criteria for obesity and 62.5% reported lifetime attempted or completed sexual assaul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Binge eating (Pagoto et al, 2011; Rohde et al, 2008) or emotional eating (using food as a way of coping; Greenfield & Marks, 2009; Schrepf et al, 2014) was examined in multiple studies and was significantly associated with ACEs but did not always meet statistical criteria for full mediation. Many studies (Alvarez, Pavao, Baumrind, & Kimerling, 2007; Boynton-Jarrett et al, 2012; Brewer-Smyth, 2014; Cheney et al, 2014; D’Argenio et al, 2009; Francis, Nikulina, & Widom, 2015; Mamun, O’Callaghan, Williams, & Najman, 2013 [defined as internalizing behaviors]) tested depression and/or anxiety symptoms as mediators, with most (but not all) findings significant. In the analysis of a subset of participants in the Study of Women’s Health Across the Nation, Midei et al (2010) found a significant mediating effect of reported anger on both BMI and waist circumference, but not for the other measures of mental health state examined (depression, anxiety, or cynicism).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binge eating (Pagoto et al, 2011; Rohde et al, 2008) or emotional eating (using food as a way of coping; Greenfield & Marks, 2009; Schrepf et al, 2014) was examined in multiple studies and was significantly associated with ACEs but did not always meet statistical criteria for full mediation. Many studies (Alvarez, Pavao, Baumrind, & Kimerling, 2007; Boynton-Jarrett et al, 2012; Brewer-Smyth, 2014; Cheney et al, 2014; D’Argenio et al, 2009; Francis, Nikulina, & Widom, 2015; Mamun, O’Callaghan, Williams, & Najman, 2013 [defined as internalizing behaviors]) tested depression and/or anxiety symptoms as mediators, with most (but not all) findings significant. In the analysis of a subset of participants in the Study of Women’s Health Across the Nation, Midei et al (2010) found a significant mediating effect of reported anger on both BMI and waist circumference, but not for the other measures of mental health state examined (depression, anxiety, or cynicism).…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral interventions such as MOVE (Managing Overweight and/or Obesity for Veterans Everywhere) should integrate assessment of psychosocial risk factors for obesity. Training on behavioral and psychosocial skills should be provided to help participants “find healthy ways to self-manage life stressors” (p. 753), with the goal of increasing adherence to diet and exercise regimes (Cheney et al, 2014, p. 753).Mechanisms should be addressed by interventions. Rather than just emphasizing nutrition and physical activity, interventions should “address ways of coping with stress and negative emotions.” Exercise reduces depressive symptoms, so interventions should encourage exercise as “a relaxing, stress-reducing activity” (Alvarez et al, 2007, p. 32).Neighborhood contextual factors should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…History of sexual assault has been linked to obesity and elevated BMI in some studies. 33 34 This is of particular concern to university students as 14%–44% report experiencing some form of sexual assault since starting undergraduate studies. 35…”
Section: Introductionmentioning
confidence: 99%
“…While many women have fulfilling and life-changing experiences within the military and achieve significant personal and professional goals (Brooks, Dailey, Bair, & Shore, 2016;Dodds, 2016), others experience significant, physical and mental health difficulties, leading to early discharge which influences their lives long after military service has ended (Cheney et al, 2014;Dichter & True, 2015;Yalch, Hebenstreit, & Maguen, 2018). Women's experiences in recent military conflicts are often found in popular literature depicting significant events of heroism such as survival behind enemy lines (Johnson & Doyle, 2010).…”
Section: Experiences During the Militarymentioning
confidence: 99%